The Effect of an Educational Field to Develop Motor Coordination and Control Skill for Football Cubs - Abdul Kareem Mezher, Aban; Gaber Mohammed , Diaa; Abd Ali Abdaoun, Amjad (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of the research is to identify the effect of the field to develop motor compatibility and control skill for the Cubs in soccer, and the researcher used the experimental approach to design the two equivalent groups (control and experimental) for the research sample of 20 players for the season 2018-2019. the researcher prepared an educational field and the researcher used the researcher The tools and devices appropriate for the research, and the researcher conducted an exploratory experiment to ensure the safety of the devices and tools, and a researcher performed the Pretests, in addition to implementing special exercises for motor compatibility and the skill of controlling football through the field prepared in advance for a period of (8) weeks, at the rate of (3) Units per week, then Or the researcher conducted meta-tests and data processing and presentation and statistical analysis and concluded that the effectiveness of the researcher's consensus motor and educational field, as well as the researcher's recommendation of the use of the educational field during the educational units for players to develop football skills, is other.